Psychological needs, self-efficacy, motivation, and resistance training outcomes in a 16-week barbell training program for adults - Martinez Kercher, Vanessa M.; Watkins, Janette M.; Goss, Janelle M.; Phillips, Liam A.; Roy, Brad A.; Blades, Kyler; Dobson, Dana; Kercher, Kyle A. (Frontiers in Psychology, 2024)
Background Despite extensive research on the relationship between psychological factors and aerobic training, there remains a gap in understanding these relationships within resistance training (RT), particularly barbell-based RT. This study aimed to examine the associations between basic psychological needs, behavioral regulation, self-efficacy, and a longitudinal barbell-based RT program for adults. Methods Forty-three adults (M age = 45.09 ± 10.72) were recruited from the Competitive Edge resistance training program at a medical fitness center in Northwest Montana. The study followed an 18-week schedule: 8 weeks of training, 1 week of active recovery, and 8 additional weeks of training. Results The results reveal several significant findings. First, the basic psychological need for competence significantly increased from baseline (M = 5.06) to post-program (M = 5.30), (p = 0.017). Second, the composite score of the BREQ-3 significantly predicting muscular strength improvements in the deadlift (β = 3.64, p = 0.039). Third, both mastery (p = 0.021) and resilience (p = 0.007) self-efficacy subscales increased from baseline to post-program. Fourth, exploratory analyses indicated that the reasons to exercise scale predicted increases in muscular endurance with the weight management (β = 10.016, p = 0.046) and solitude (β = 6.792, p = 0.037) subscales. Conclusion These findings highlight the importance of psychological factors in predicting strength outcomes and muscular endurance, suggesting that psychological interventions may complement physical training to maximize benefits. This research contributes valuable insights into how psychological factors influence training outcomes, potentially guiding future interventions and program designs to better support strength development and endurance in resistance training contexts.